2007
DOI: 10.1358/mf.2007.29.1.1063490
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of the urea transporter gene are associated with antihypertensive response to nifedipine GITS

Abstract: Nifedipine GITS has diuretic and natriuretic properties, which may enhance its antihypertensive efficacy. We assessed contributions of polymorphisms in the urea transporter-A gene (SLC14A2) to interindividual variations in blood pressure (BP) response to nifedipine treatment. 405 subjects from a single Chinese county received a single oral dose of 30 mg nifedipine GITS (gastrointestinal therapeutic system) daily for 16 days. We genotyped two SNPs in SLC14A2 and found significant associations for the Val227Ile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The importance of microvascular function is emphasised by the solute carrier transporters such as SLC14A2 encoding a urea transporter, which has previously been linked to autosomal dominant Streeten type orthostatic hypotensive disorder 41 and BP response to nifedipine, a calcium channel blocker antihypertensive drug 42 . SLC8A1 encodes a sodium calcium exchanger expressed in cardiomyocytes which alters cardiac contractility and hypertrophy and shows abnormal BP in SLC8A1 transgenic mice 43 .…”
Section: Discussionmentioning
confidence: 99%
“…The importance of microvascular function is emphasised by the solute carrier transporters such as SLC14A2 encoding a urea transporter, which has previously been linked to autosomal dominant Streeten type orthostatic hypotensive disorder 41 and BP response to nifedipine, a calcium channel blocker antihypertensive drug 42 . SLC8A1 encodes a sodium calcium exchanger expressed in cardiomyocytes which alters cardiac contractility and hypertrophy and shows abnormal BP in SLC8A1 transgenic mice 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Several polymorphisms of UT-A2 have been identified in humans. Although the functional consequence of these variants on urea transport have not been explored to our knowledge, epidemiological studies in large populations revealed that some of these variants are associated with blood pressure and metabolic syndrome, [217][218][219] suggesting that UT-A2 and renal urea handling influence fluid balance in humans. New studies should address the function of these variants and attempt to better define the contribution of UT-A2 to overall urea handling.…”
Section: Discussionmentioning
confidence: 99%
“…Other 3 SNPs (rs1825475, rs1484873, and rs7232775) in SLC14A2 on chromosome 18 were known to be associated with serum creatinine and GFR [ 15 ]. rs1484873 and rs7232775 in SLC14A2 on chromosome 18 were also associated with BUN and hypertension [ 16 , 17 ]. rs10937329 in an intergenic region was the lead SNP on chromosome 3 associated with BUN.…”
Section: Discussionmentioning
confidence: 99%